The second chance boutique : a novel - Leaman, Louisa (Sourcebooks Landmark, 2020)
"Francesca Delaney's wedding gown shop has two necessary rules to guarantee success: 1. Never covet a dress 2. Never sell a dress that led to a doomed marriage. These two rules have helped Francesca build her reputation as a woman with a knack for matching a bride-to-be with the perfect gown. At Fran's shop every gown has its history, and the dresses seem to whisper their secrets to Fran, telling her the perfect match. But Francesca breaks both these rules the day she finds a beautiful 1950s couture floor-length gown. In her desperation to know the dress's background she inadvertently becomes entangled with the original owner's son, who would like the dark history of the dress to remain hidden forever"--